High-energy-absorption flame-retardant foam magnesium alloy as well as preparation method and application thereof

By using specific element combinations and foaming agents in foam magnesium alloys and combining precise process control, the problems of traditional foam magnesium alloys are solved, high cost and uneven pores at high temperatures, and high energy-absorbing and flame-retardant foam magnesium foam is achieved Alloy preparation, suitable for a variety of high-performance applications.

CN119392064APending Publication Date: 2025-02-07JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411489783.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional foam magnesium alloys are flammable in high temperature environments, have high production costs, complex processes and uneven pore structures, making it difficult to meet the application needs of high energy absorption and flame retardant properties.

Method used

Use elements such as aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium as metal matrix, combining foaming agents such as calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate, as well as magnesium oxide, alumina and silicon Taxi-increasing agents such as aluminum acid are prepared by precisely controlling the temperature and component ratio, heat treatment, cooling treatment and annealing, and high energy absorption and flame retardant foam magnesium alloys.

Benefits of technology

It realizes uniformity and durability of pore structure, reduces production costs, simplifies process flow, improves the energy absorption and flame retardancy of materials, and is suitable for a variety of high-performance application scenarios such as aerospace, automobiles, and building sound insulation walls. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099701570000091
    Figure BDA0005099701570000091
  • Figure BDA0005099701570000101
    Figure BDA0005099701570000101
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium alloy materials, and discloses a high-energy-absorption flame-retardant foam magnesium alloy and a preparation method and application thereof.The preparation method of the high-energy-absorption flame-retardant foam magnesium alloy comprises the following steps that aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium are molten to obtain a molten metal matrix; mixing the molten metal matrix with a tackifier to obtain a composite melt; and the composite melt and a foaming agent are mixed and then subjected to heat treatment, cooling treatment and annealing in sequence, and the high-energy-absorption flame-retardant foam magnesium alloy is obtained. According to the preparation method, dependence on rare earth elements is reduced, the production cost is reduced, the pore structure can be effectively stabilized, and the preparation process is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloy materials, and in particular to a high energy absorption flame retardant foam magnesium alloy and a preparation method and application thereof. Background Art

[0002] Due to its light weight, high specific strength and excellent energy absorption capacity, magnesium alloy foam has attracted wide attention in the fields of aerospace, automobile, shipbuilding, etc. However, the traditional magnesium alloy foam materials still have the following problems in practical applications: First, although magnesium alloy foam has certain energy absorption performance, its easy combustion in high temperature environment limits its use in high temperature or fireproof occasions; second, the conventional foaming process is difficult to ensure the uniform and durable pore morphology of magnesium alloy foam, which directly affects the energy absorption performance and long-term structural stability of the material.

[0003] In order to solve the above problems, the prior art has proposed some improvement schemes. For example, patents (CN101608278A) and (CN1737173A) significantly improve the flame retardancy of the material by adding rare earth elements (such as yttrium and dysprosium) to magnesium alloys. However, these rare earth elements are expensive, resulting in high material costs and difficulty in large-scale promotion. Patent (CN116043083A) proposes to add a large amount of rare earth elements gadolinium and aluminum to make the alloy absorb a large amount of gas during the smelting process, and to precipitate the gas by controlling the solidification conditions, thereby self-foaming to form a foam structure. However, this method is difficult to accurately control the formation and morphology of pores, and the use of a large amount of rare earth elements still has the problem of high cost. The uniformity and durability of pores are still one of the key problems in improving the energy absorption performance of foamed magnesium alloys, and cannot meet higher application requirements.

[0004] Therefore, it is of great significance to study a high energy absorption flame retardant foam magnesium alloy with good pore uniformity, excellent energy absorption capacity and strong durability, as well as its preparation method and application. Summary of the invention

[0005] In view of this, the present invention provides a high energy absorption flame retardant foam magnesium alloy and a preparation method and application thereof, the purpose of which is to overcome the problems of the prior art that the foam magnesium alloy is flammable at high temperatures, has high preparation cost, complex process and uneven pore structure.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a high energy absorption flame retardant foam magnesium alloy, comprising the following components: a metal matrix, a foaming agent and a tackifier;

[0008] The metal matrix includes aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium.

[0009] Preferably, the metal matrix comprises the following components in mass fractions: 1-5% aluminum, 1-5% bismuth, 0.5-2% tin, 0.5-2% zinc, 0.5-2% manganese, 0.1-0.5% cobalt, 0.1-1% calcium, 0.1-0.5% beryllium, and the rest is magnesium.

[0010] Preferably, the foaming agent comprises calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate; the mass ratio of the calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate is 30-40:20-30:10-20:20-30.

[0011] Preferably, the viscosity enhancer comprises magnesium oxide, aluminum oxide and aluminum silicate; the mass ratio of magnesium oxide, aluminum oxide and aluminum silicate is 40-50:25-35:20-30.

[0012] Preferably, the mass ratio of the metal matrix, the foaming agent and the tackifier is 82-96:1-6:3-12.

[0013] The present invention also provides a method for preparing the high energy absorption flame retardant foamed magnesium alloy, comprising the following steps:

[0014] (1) melting aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium to obtain a molten metal matrix;

[0015] (2) mixing a molten metal matrix with a viscosity enhancer to obtain a composite melt;

[0016] (3) The composite melt is mixed with a foaming agent and subjected to heat treatment, cooling treatment and annealing in sequence to obtain a highly energy-absorbing flame-retardant magnesium alloy foam.

[0017] Preferably, in step (1), the melting temperature is 650-700° C., and the melting time is 5-15 min;

[0018] In the step (2), the mixing temperature is 650-700° C., and the mixing time is 14-40 minutes.

[0019] Preferably, in step (3), the heat treatment includes a first heat treatment and a second heat treatment;

[0020] In the first heat treatment, the temperature is 680-700°C and the time is 5-10 minutes;

[0021] In the second heat treatment, the temperature is 700-750° C. and the time is 10-15 minutes.

[0022] Preferably, in step (3), the cooling treatment includes a first cooling treatment and a second cooling treatment;

[0023] In the first cooling treatment, the temperature is 480-550°C and the time is 2-6 minutes;

[0024] In the second cooling treatment, the temperature is 20-30°C;

[0025] The annealing temperature is 180-250°C, and the annealing time is 4-12 hours.

[0026] The present invention also provides the use of the high energy absorption flame retardant foam magnesium alloy in energy absorption flame retardant materials, and the energy absorption flame retardant materials include aerospace materials, automobile materials, ship materials, building sound insulation wall materials and industrial protection materials.

[0027] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0028] The preparation method of the present invention not only reduces the dependence on rare earth elements and reduces production costs, but also effectively stabilizes the pore structure and simplifies the preparation process. In addition, through reasonable component ratio and temperature control, precise regulation of the pore structure is achieved, so that the foamed magnesium alloy has better energy absorption and flame retardancy, and is more suitable for a variety of application scenarios requiring high energy absorption and flame retardancy, such as aerospace, automobiles, and building sound insulation walls.

[0029] The present invention successfully increases the viscosity of the melt by introducing a mixture of magnesium oxide, aluminum oxide and aluminum silicate as a tackifier, so that the bubbles can be kept stable during the foaming process, significantly reducing the probability of bubble merging. In addition, precise temperature control and the use of a gradually decomposed foaming agent make the pore structure of the foamed magnesium alloy more uniform, overcoming the difficulty of traditional processes in controlling pore morphology. Furthermore, the uniform pore structure and appropriate porosity improve the energy absorption capacity of the material, making it suitable for use under high impact load conditions; the flame retardant elements in the alloy components and the oxides produced during the foaming process can form a protective layer in a high temperature environment to inhibit combustion. DETAILED DESCRIPTION

[0030] The present invention provides a high energy absorption flame retardant foam magnesium alloy, comprising the following components: a metal matrix, a foaming agent and a tackifier;

[0031] The metal matrix includes aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium.

[0032] In the present invention, the metal matrix includes the following components in mass fraction: the mass fraction of aluminum is preferably 1-5%, more preferably 2-4%, and more preferably 3%; the mass fraction of bismuth is preferably 1-5%, more preferably 2-4%, and more preferably 3%; the mass fraction of tin is preferably 0.5-2%, and more preferably 1-1.5%; the mass fraction of zinc is preferably 0.5-2%, and more preferably 1-1.5%; the mass fraction of manganese is preferably 0.5-2%, and more preferably 1-1.5%; the mass fraction of cobalt is preferably 0.1-0.5%, and more preferably 0.2-0.4%, and more preferably 0.3%; the mass fraction of calcium is preferably 0.1-1%, and more preferably 0.3-0.8%, and more preferably 0.5-0.6%; the mass fraction of beryllium is preferably 0.1-0.5%, and more preferably 0.2-0.4%, and more preferably 0.3%; and the rest is magnesium.

[0033] In the present invention, the addition of bismuth, calcium, beryllium and cobalt not only reduces the cost of the alloy, but also significantly improves the flame retardancy and the stability of the pore structure; beryllium, bismuth and calcium help to form a high temperature resistant protective layer, while cobalt and calcium play an important role in improving mechanical properties and enhancing the thermal stability of the alloy. In addition, the synergistic effect of these elements enables excellent flame retardancy to be achieved without relying on rare earth elements.

[0034] In the present invention, the foaming agent preferably includes calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate; the mass ratio of the calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate is preferably 30-40:20-30:10-20:20-30, more preferably 32-38:22-28:12-18:22-28, and more preferably 34-36:24-26:14-16:24-26.

[0035] In the present invention, the viscosity enhancer preferably includes magnesium oxide, aluminum oxide and aluminum silicate; the mass ratio of magnesium oxide, aluminum oxide and aluminum silicate is preferably 40-50:25-35:20-30, more preferably 42-48:27-33:22-28, and more preferably 44-46:29-31:24-26.

[0036] In the present invention, the mass ratio of the metal substrate, the foaming agent and the tackifier is preferably 82-96:1-6:3-12, more preferably 86-94:2-5:5-10, and more preferably 88-90:3-4:6-8.

[0037] In the present invention, the combination of the foaming agent and the viscosity enhancer not only simplifies the foaming process, but also significantly improves the uniformity and structural stability of the pores during the foaming process; this combination effectively supports the formation of bubbles, avoids premature rupture or merging of bubbles during high-temperature foaming, and improves the energy absorption performance and flame retardant effect of the material.

[0038] The present invention also provides a method for preparing the high energy absorption flame retardant foamed magnesium alloy, comprising the following steps:

[0039] (1) melting aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium to obtain a molten metal matrix;

[0040] (2) mixing a molten metal matrix with a viscosity enhancer to obtain a composite melt;

[0041] (3) The composite melt is mixed with a foaming agent and subjected to heat treatment, cooling treatment and annealing in sequence to obtain a highly energy-absorbing flame-retardant magnesium alloy foam.

[0042] In the present invention, the step (1) is preferably to first melt magnesium, then add aluminum, bismuth, tin, zinc and manganese under stirring, and then add calcium, beryllium and cobalt after the aluminum, bismuth, tin, zinc and manganese are melted, so as to obtain a molten metal matrix after melting.

[0043] In the present invention, in the step (1), the melting temperature is preferably 650-700°C, more preferably 660-690°C, more preferably 670-680°C, and the melting time is preferably 5-15 min, more preferably 7-13 min, more preferably 10-12 min; the stirring rate is preferably 300-500 rpm, more preferably 350-450 rpm, more preferably 400-420 rpm, and the stirring rate can ensure uniform distribution of elements in the molten metal without generating excessive bubbles or unstable vortices.

[0044] In the present invention, the step (2) is preferably to add equal amounts of the thickener to the molten metal matrix multiple times, and after the addition is completed, continue stirring to obtain a composite melt; the stirring rate is preferably 200-400rpm, more preferably 250-350rpm, and more preferably 280-300rpm. The stirring rate can ensure that the thickener is fully mixed with the molten metal matrix, while avoiding the formation of excessive bubbles at high temperatures, thereby ensuring the uniformity of the composite melt; the number of multiple additions is preferably 3-6 times, and more preferably 4-5 times. After each addition, it is preferably stirred for 3-5 minutes, and more preferably 4 minutes, to form a stable suspension state, ensure uniform distribution of the thickener, and increase the melt viscosity. The continuous stirring time is preferably 5-10 minutes, and more preferably 6-9 minutes, and more preferably 7-8 minutes, to ensure uniform distribution of the thickener and increase the melt viscosity, thereby enhancing the stability of the bubbles and avoiding premature rupture of the bubbles in the subsequent foaming process.

[0045] In the present invention, in step (2), the mixing temperature is preferably 650-700°C, more preferably 660-690°C, more preferably 670-680°C, and the mixing time is preferably 14-40 min, more preferably 18-36 min, more preferably 24-30 min.

[0046] In the present invention, in step (3), the heat treatment preferably includes a first heat treatment and a second heat treatment;

[0047] In the first heat treatment, the temperature is preferably 680-700°C, more preferably 685-695°C, more preferably 690-692°C, and the time is preferably 5-10 min, more preferably 6-9 min, more preferably 7-8 min;

[0048] In the second heat treatment, the temperature is preferably 700-750° C., more preferably 710-740° C., more preferably 720-730° C., and the time is preferably 10-15 min, more preferably 11-14 min, more preferably 12-13 min.

[0049] In the present invention, the first heat treatment allows sodium bicarbonate to be preferentially decomposed to generate initial bubbles and form a basic pore structure; the second heat treatment gradually decomposes calcium carbonate, aluminum carbonate and magnesium carbonate to provide continuous gas release at a higher temperature and prevents bubble merging through the support of a thickener; the heat treatment is controlled to be completed within 15 to 25 minutes to ensure smooth gas release and uniform pore structure.

[0050] In the present invention, in the step (3), the cooling treatment preferably includes a first cooling treatment and a second cooling treatment;

[0051] In the first cooling treatment, the temperature is preferably 480-550°C, more preferably 490-530°C, more preferably 500-520°C, and the time is preferably 2-6 min, more preferably 3-5 min, more preferably 4 min;

[0052] In the second cooling treatment, the temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 24-26°C;

[0053] In the present invention, the first cooling treatment slowly cools the foamed molten alloy to 480-550°C, thereby maintaining the stability of the bubble structure and avoiding pore collapse; the second cooling treatment ensures the density and uniformity of the bubble wall, stabilizes the overall structure of the alloy, and finally controls the porosity at 50-80%, the average pore size is 0.1-3.5 mm, and the standard deviation of the pore size distribution is less than 1.2 mm; most of the pore morphology is approximately spherical closed pores, and there are about 15% open pore structures. This pore morphology design provides a certain air permeability while ensuring structural stability.

[0054] The annealing temperature is preferably 180-250°C, more preferably 190-240°C, more preferably 200-220°C, and the annealing time is preferably 4-12h, more preferably 6-10h, more preferably 7-8h; the annealing further releases the residual stress inside the material, improves the toughness and ductility of the bubble wall, and enhances the stability of the bubble wall structure; at the same time, it promotes the formation of precipitation phase, significantly improving the strength, hardness and energy absorption characteristics of the foam alloy.

[0055] In the present invention, cooling is performed after annealing, and the cooling temperature is 20-30°C, more preferably 22-28°C, and more preferably 24-26°C; after annealing, it is slowly cooled to room temperature to achieve uniformity and durability of the bubble wall, ensuring that the foamed magnesium alloy has excellent energy absorption characteristics and overall stability.

[0056] The present invention also provides the use of the high energy absorption flame retardant foam magnesium alloy in energy absorption flame retardant materials, and the energy absorption flame retardant materials include aerospace materials, automobile materials, ship materials, building sound insulation wall materials and industrial protection materials.

[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Example 1

[0059] In this embodiment, the mass ratio of the metal matrix, the foaming agent and the tackifier is 92:3:5; the metal matrix includes the following components by mass fraction: 3% aluminum, 3% bismuth, 1% tin, 1% zinc, 1% manganese, 0.5% calcium, 0.5% beryllium, 0.5% cobalt, and the rest is magnesium; the tackifier is composed of magnesium oxide, aluminum oxide and aluminum silicate in a mass ratio of 50:30:20; the foaming agent is composed of calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate in a mass ratio of 35:25:15:25;

[0060] The steps for preparing the high energy absorption flame retardant magnesium alloy foam in this embodiment are as follows:

[0061] Magnesium with a purity of 99.5% is placed in a crucible and heated to 700°C. After melting, aluminum, bismuth, tin, zinc and manganese are added under stirring at a speed of 420 rpm. After melting, calcium, beryllium and cobalt are added. After stirring at the original speed for 10 minutes, a molten metal matrix is ​​obtained.

[0062] The molten metal matrix is ​​maintained at 680°C, and the viscosity enhancer is added in equal amounts in 5 times in the molten state, and stirred at a speed of 280 rpm for 3 minutes after each addition. After the addition is completed, stirring is continued at the original speed for 8 minutes to obtain a composite melt;

[0063] A foaming agent is added to the obtained composite melt for heat treatment, and the heat treatment process is as follows: heating to 690°C and maintaining for 8 minutes, then heating to 720°C and maintaining for 10 minutes, cooling to 500°C after the heat treatment process is completed, and maintaining for 3 minutes, and then cooling to 25°C to obtain a foamed magnesium alloy; the obtained foamed magnesium alloy is heated to 200°C, annealed for 8 hours, and then cooled to 25°C to obtain a high energy absorption and flame retardant foamed magnesium alloy.

[0064] Example 2

[0065] In this embodiment, the mass ratio of the metal matrix, the foaming agent and the tackifier is 88:4:8; the metal matrix includes the following components by mass fraction: 4% aluminum, 2% bismuth, 1.5% tin, 1.5% zinc, 0.5% manganese, 0.8% calcium, 0.3% beryllium, 0.4% cobalt, and the rest is magnesium; the tackifier is composed of magnesium oxide, aluminum oxide and aluminum silicate in a mass ratio of 45:30:25; the foaming agent is composed of calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate in a mass ratio of 38:25:12:25;

[0066] The steps for preparing the high energy absorption flame retardant magnesium alloy foam in this embodiment are as follows:

[0067] Magnesium with a purity of 99.8% is placed in a crucible and heated to 700°C. After melting, aluminum, bismuth, tin, zinc and manganese are added under stirring at a speed of 420 rpm. After melting, calcium, beryllium and cobalt are added. After stirring at the original speed for 15 minutes, a molten metal matrix is ​​obtained.

[0068] The molten metal matrix is ​​maintained at 700°C, and the tackifier is added in equal amounts in 6 times in the molten state. After each addition, the mixture is stirred at a speed of 280 rpm for 5 minutes. After the addition is completed, the mixture is stirred at the original speed for 10 minutes to obtain a composite melt.

[0069] A foaming agent is added to the obtained composite melt for heat treatment, and the heat treatment process is as follows: heating to 700°C and maintaining for 8 minutes, then heating to 740°C and maintaining for 15 minutes, cooling to 520°C after the heat treatment process is completed, and maintaining for 5 minutes, and then cooling to 23°C to obtain a foamed magnesium alloy; the obtained foamed magnesium alloy is heated to 220°C, annealed for 6 hours, and then cooled to 23°C to obtain a high energy absorption and flame retardant foamed magnesium alloy.

[0070] Example 3

[0071] In this embodiment, the mass ratio of the metal matrix, the foaming agent and the tackifier is 89:4:7; the metal matrix includes the following components by mass fraction: 4.5% aluminum, 3.5% bismuth, 1.5% tin, 1% zinc, 0.8% manganese, 0.8% calcium, 0.4% beryllium, 0.3% cobalt, and the rest is magnesium; the tackifier is composed of magnesium oxide, aluminum oxide and aluminum silicate in a mass ratio of 45:35:20; the foaming agent is composed of calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate in a mass ratio of 30:25:15:30;

[0072] The steps for preparing the high energy absorption flame retardant magnesium alloy foam in this embodiment are as follows:

[0073] Magnesium with a purity of 99.8% is placed in a crucible and heated to 720°C. After melting, aluminum, bismuth, tin, zinc and manganese are added under stirring at a speed of 420 rpm. After melting, calcium, beryllium and cobalt are added. After stirring at the original speed for 10 minutes, a molten metal matrix is ​​obtained.

[0074] The molten metal matrix is ​​maintained at 690°C, and the viscosity enhancer is added in equal amounts in 5 times in the molten state, and stirred at a speed of 280 rpm for 5 minutes after each addition. After the addition is completed, stirring is continued at the original speed for 10 minutes to obtain a composite melt;

[0075] A foaming agent is added to the obtained composite melt for heat treatment, and the heat treatment process is as follows: heating to 690°C and maintaining for 8 minutes, then heating to 730°C and maintaining for 10 minutes, cooling to 500°C after the heat treatment process is completed and maintaining for 5 minutes, and then cooling to 24°C to obtain a foamed magnesium alloy; the obtained foamed magnesium alloy is heated to 220°C, annealed for 6 hours, and then cooled to 24°C to obtain a high energy absorption and flame retardant foamed magnesium alloy.

[0076] Comparative Example 1

[0077] In this comparative example, the mass ratio of the metal matrix to the foaming agent is 96:4; the metal matrix includes the following components by mass fraction: 3% aluminum, 1% zinc, and the rest magnesium; the foaming agent is calcium carbonate;

[0078] The preparation steps of the magnesium alloy foam in this comparative example are as follows:

[0079] 99.9% pure magnesium was heated to 700°C, aluminum and zinc were added, and stirred at 420 rpm for 10 minutes to obtain a molten metal matrix;

[0080] Then, a foaming agent is added to the molten metal matrix at 680°C, heated to 750°C and then cooled to room temperature to obtain a foamed magnesium alloy.

[0081] Performance Test:

[0082] Pore ​​morphology test: The average pore size, porosity and pore morphology of the foamed magnesium alloys obtained in Examples 1 to 3 and Comparative Example 1 were tested. The test results are shown in Table 1.

[0083] Energy absorption capacity test: At a compression rate of 50%, the energy absorption capacity of the high energy absorption flame retardant magnesium alloy foams obtained in Examples 1 to 3 and the magnesium alloy foam obtained in Comparative Example 1 was tested respectively. The test results are shown in Table 1.

[0084] Compression strength test: At a compression rate of 50%, the compression strengths of the high energy absorption and flame retardant magnesium alloy foams obtained in Examples 1 to 3 and the magnesium alloy foam obtained in Comparative Example 1 were tested respectively. The test results are shown in Table 1.

[0085] Ignition point test: The ignition points of the high energy absorption flame retardant magnesium alloy foams obtained in Examples 1 to 3 and the magnesium alloy foam obtained in Comparative Example 1 were tested respectively. The test results are shown in Table 1.

[0086] Table 1 Performance test results of the high energy absorption flame retardant magnesium alloy foam obtained in Examples 1 to 3 and the magnesium alloy foam obtained in Comparative Example 1

[0087]

[0088]

[0089] As can be seen from Table 1, the high energy absorption flame retardant magnesium alloy foam prepared by the present invention is superior to the prior art in terms of energy absorption, flame retardancy and mechanical properties, and has lower production costs and a simpler process flow, and is suitable for various applications requiring high-performance materials. Example 1 is more suitable for high energy absorption occasions, while Examples 2 and 3 are more suitable for occasions with higher requirements for material strength and high temperature performance.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A highly energy-absorbing flame-retardant magnesium alloy foam, characterized in that: The invention comprises the following components: a metal matrix, a foaming agent and a tackifier; The metal matrix includes aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium.

2. The high energy absorption flame retardant foamed magnesium alloy according to claim 1, characterized in that: The metal matrix comprises the following components in mass fraction: 1-5% aluminum, 1-5% bismuth, 0.5-2% tin, 0.5-2% zinc, 0.5-2% manganese, 0.1-0.5% cobalt, 0.1-1% calcium, 0.1-0.5% beryllium, and the rest is magnesium.

3. The high energy absorption flame retardant foamed magnesium alloy according to claim 2, characterized in that: The foaming agent comprises calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate; the mass ratio of the calcium carbonate, aluminum carbonate, sodium bicarbonate and magnesium carbonate is 30-40:20-30:10-20:20-30.

4. A highly energy-absorbing flame-retardant foamed magnesium alloy according to claim 2 or 3, characterized in that: The viscosity enhancer comprises magnesium oxide, aluminum oxide and aluminum silicate; the mass ratio of magnesium oxide, aluminum oxide and aluminum silicate is 40-50:25-35:20-30.

5. The high energy absorption flame retardant foamed magnesium alloy according to claim 4, characterized in that: The mass ratio of the metal matrix, the foaming agent and the tackifier is 82-96:1-6:3-12.

6. The method for preparing the high energy absorption flame retardant foamed magnesium alloy according to any one of claims 1 to 5, characterized in that: The steps include: (1) melting aluminum, bismuth, tin, zinc, manganese, cobalt, calcium, beryllium and magnesium to obtain a molten metal matrix; (2) mixing a molten metal matrix with a viscosity enhancer to obtain a composite melt; (3) The composite melt is mixed with a foaming agent and subjected to heat treatment, cooling treatment and annealing in sequence to obtain a highly energy-absorbing flame-retardant magnesium alloy foam.

7. The method for preparing a highly energy-absorbing flame-retardant magnesium alloy foam according to claim 6, characterized in that: In the step (1), the melting temperature is 650-700° C. and the melting time is 5-15 min; In the step (2), the mixing temperature is 650-700° C., and the mixing time is 14-40 minutes.

8. The method for preparing a highly energy-absorbing flame-retardant magnesium alloy foam according to claim 7, characterized in that: In the step (3), the heat treatment includes a first heat treatment and a second heat treatment; In the first heat treatment, the temperature is 680-700°C and the time is 5-10 minutes; In the second heat treatment, the temperature is 700-750° C. and the time is 10-15 minutes.

9. A method for preparing a highly energy-absorbing flame-retardant foamed magnesium alloy according to claim 6 or 8, characterized in that: In the step (3), the cooling treatment includes a first cooling treatment and a second cooling treatment; In the first cooling treatment, the temperature is 480-550°C and the time is 2-6 minutes; In the second cooling treatment, the temperature is 20-30°C; The annealing temperature is 180-250°C, and the annealing time is 4-12 hours.

10. Use of the highly energy-absorbing flame-retardant foamed magnesium alloy according to any one of claims 1 to 5 in energy-absorbing flame-retardant materials, characterized in that: The energy-absorbing flame-retardant materials include aerospace materials, automobile materials, ship materials, building sound insulation wall materials and industrial protection materials.

Citation Information

Patent Citations

  • Flame-retardant foam magnesium alloy and preparation method thereof

    CN101608278A

  • Self-foaming in-situ synthesis particle reinforced high-modulus foam magnesium alloy and preparation method thereof

    CN116043083A

  • Magnesium alloy flame-proof additive and flame-proof magnesium alloy preparation method

    CN1737173A